Dapagliflozin in patients with heart failure with mildly reduced and preserved ejection fraction treated with a mineralocorticoid receptor antagonist or sacubitril/valsartan. (7th November 2022) - Yang, Mingming; Butt, Jawad H.; Kondo, Toru; Jering, Karola S.; Docherty, Kieran F.; Jhund, Pardeep S.; de Boer, Rudolf A.; Claggett, Brian L.; Desai, Akshay S.; Hernandez, Adrian F.; Inzucchi, Silvio E.; Kosiborod, Mikhail N.; et al.
ABSTRACT: Aims: The effects of adding a sodium–glucose cotransporter 2 (SGLT2) inhibitor to a mineralocorticoid receptor antagonist (MRA) or an angiotensin receptor–neprilysin inhibitor (ARNI) in patients with heart failure (HF) and mildly reduced ejection fraction (HFmrEF) and preserved ejection fraction (HFpEF) are uncertain, even though the use of all three drugs is recommended in recent guidelines. Methods and results: The efficacy and safety of dapagliflozin added to background MRA or ARNI therapy was examined in patients with HFmrEF/HFpEF enrolled in the DELIVER trial. The primary outcome was the composite of worsening HF or cardiovascular death. Of 6263 patients, 2667 (42.6%) were treated with an MRA and 301 (4.8%) with an ARNI at baseline. Patients taking either were younger, more often men and had lower systolic blood pressure and ejection fraction; they were also more likely to have prior HF hospitalization. The benefit of dapagliflozin was similar whether patients were receiving these therapies. The hazard ratio for the effect of dapagliflozin compared to placebo on the primary outcome was 0.86 (95% confidence interval [CI] 0.74–1.01) for MRA non‐users versus 0.76 (95% CI 0.64–0.91) for MRA users ( p interaction = 0.30). The corresponding values for ARNI non‐users and users were 0.82 (95% CI 0.73–0.92) and 0.74 (95% CI 0.45–1.22), respectively ( p interaction = 0.75). None of the adverse events examined was more common with dapagliflozin compared to placebo overall or in the MRA and ARNI subgroups. Conclusions: The efficacy and safety of dapagliflozin were similar, regardless of background treatment with an MRA or ARNI. SGLT2 inhibitors may be added to other treatments recommended in recent guidelines for HFmrEF/HFpEF. Abstract : Effects of dapagliflozin in patients taking or not taking a mineralocorticoid receptor antagonist (MRA) and an angiotensin receptor–neprilysin inhibitor (ARNI). CI, confidence interval; CV, cardiovascular; HF, heart failure; HFmrEF, heart failure with mildly reduced ejection fraction; HFpEF, heart failure with preserved ejection fraction; hosp., hospitalization.